An Updated View of Cisplatin Transport. Issue 15 (14th May 2013) - Arnesano, Fabio; Losacco, Maurizio; Natile, Giovanni
Abstract: Invited for the cover of this issue is the group of Giovanni Natile at the University of Bari. The cover image poses the question whether platinum exchange occurs between transporters as it happens for copper – a major question still lacking an answer. In the background is "the near‐touching hands", a detail of the Creation of Adam by Michelangelo. Abstract : The most exciting aspect of Bioinorganic Chemistry is the deep involvement of different areas of expertise, spanning from basic inorganic chemistry to life sciences, complemented by the use of the most advanced spectroscopic techniques such as in‐cell NMR spectroscopy... This and more about the story behind the cover in theCover Profile and about the research itself onp. 2701 ff .